Life cycle cost assessment of electric vehicles: A review and bibliometric analysis - Ayodele B.V.; Mustapa S.I. (MDPI, 2023)
competitiveness; cost analysis; electric vehicle; engine; global warming; life cycle analysis; literature review; Scopus